DIGITAL CURRENCY AS A FACTOR IN TRANSFORMING THE LEGAL STATUS OF NON-CASH FUNDS - KROKHINA Yulia Aleksandrovna (Правовое государство: теория и практика)
In the digital economy, the financial sphere and money are undergoing rapid changes, which entails the transformation of their legal regulation. Changes are taking place not only in settlement forms and banking models, but also in the payment instruments themselves. The purpose of the article is to clearly distinguish the concepts of official and non-official payment instruments in order to ensure safe and stable money circulation. Empirical methods of comparison and observation; theoretical methods of analysis, formal and dialectical logics are used in the preparation of the article. Results: the article reveals that digital transformation of economy has caused the emergence of a new type of currency as a means of payment. The article substantiates that non-cash funds are the object of absolute legal relations, non-material property and represent a special absolute right .